Keloid Scarring: Understanding the Genetic Basis, Advances, and Prospects - Halim, Ahmad Sukari; Emami, Azadeh; Salahshourifar, Iman; Kannan, Thirumulu Ponnuraj (Korean Society of Plastic and Reconstructive Surgeons, 2012)
Keloid disease is a fibroproliferative dermal tumor with an unknown etiology that occurs after a skin injury in genetically susceptible individuals. Increased familial aggregation, a higher prevalence in certain races, parallelism in identical twins, and alteration in gene expression all favor a remarkable genetic contribution to keloid pathology. It seems that the environment triggers the disease in genetically susceptible individuals. Several genes have been implicated in the etiology of keloid disease, but no single gene mutation has thus far been found to be responsible. Therefore, a combination of methods such as association, gene-gene interaction, epigenetics, linkage, gene expression, and protein analysis should be applied to determine keloid etiology.